„Pandi-Project”. Narracyjna metabolizacja doświadczenia w „Dziennikach czasu pandemii” - Tokarska, Urszula; Ruczaj, Joanna (Człowiek i Społeczeństwo, 2023)
The presented research is a part of the broader project carried out in Poland to reconstruct the ways of experiencing the first wave of the COVID-19 Pandemic. Personal documents were obtained from psychology students elaborating daily their current experience in a written form – using proposed patterns (narrative “Subjective Figures”). The semantic analysis of 30 “Pandi-Diaries” was conducted by coders according to our Coding Sheet on three levels of text organization: content analysis, formal and meaning-making aspects. The results confirm other researchers’ reports about the visible domination of “avoiding” and/or “task-oriented” responses to the COVID-19 Pandemic’s first wave. Parallelly, results indicate the incomplete competencies of our Diaries’ Authors in their differentiation of internal states, and a kind of resistance in the use of the developmental potentiality which transcends survive and social adaptation tasks. The results can be applied in counselling, psychotherapy and supporting life-long “existential resilience” deep education activities.